Laboratory-confirmed respiratory infections as triggers for acute myocardial infarction and stroke: a self-controlled case series analysis of national linked datasets from Scotland. Issue 3 (29th March 2018) - Warren-Gash, Charlotte; Blackburn, Ruth; Whitaker, Heather; McMenamin, Jim; Hayward, Andrew C.
While acute respiratory tract infections can trigger cardiovascular events, the differential effect of specific organisms is unknown. This is important to guide vaccine policy. Using national infection surveillance data linked to the Scottish Morbidity Record, we identified adults with a first myocardial infarction or stroke from January 1, 2004 to December 31, 2014 and a record of laboratory-confirmed respiratory infection during this period. Using self-controlled case series analysis, we generated age- and season-adjusted incidence ratios (IRs) for myocardial infarction (n=1227) or stroke (n=762) after infections compared with baseline time. We found substantially increased myocardial infarction rates in the week after Streptococcus pneumoniae and influenza virus infection: adjusted IRs for days 1–3 were 5.98 (95% CI 2.47–14.4) and 9.80 (95% CI 2.37–40.5), respectively. Rates of stroke after infection were similarly high and remained elevated to 28 days: day 1–3 adjusted IRs 12.3 (95% CI 5.48–27.7) and 7.82 (95% CI 1.07–56.9) for S. pneumoniae and influenza virus, respectively. Although other respiratory viruses were associated with raised point estimates for both outcomes, only the day 4–7 estimate for stroke reached statistical significance. We showed a marked cardiovascular triggering effect of S. pneumoniae and influenza virus, which highlights the need for adequate pneumococcal and influenza vaccine uptake. Further research is needed into vascular effects of noninfluenza respiratory viruses. Laboratory-confirmed respiratory infections are linked to strokes and heart attacks in a Scottish population http://ow.ly/loOh30iyq0i